2020
DOI: 10.35940/ijitee.d9072.029420
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Microstructural Behavior of Expansive Soil Treated with Limed Leather Waste Ash

Niraj Singh Parihar*,
Ashok Kumar Gupta

Abstract: Expansive clays are one of the most widely found soil type across the globe known for their low strength behavior. A number of studies have been conducted in the past few decades to stabilize such soils using various additives. The traditional stabilizers such as cement and lime not only prove quite costly due to their high industrial demands but also result in exhaustion of the available natural resources. This study is based on admixture of a waste originating from leather industry known as limed leather was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Microstructural properties of materials can be determined in the laboratory by conducting a scanning electron microscopy (SEM) analysis, energy dispersive X-ray (EDX) analysis, radar detection, or a Mises strain test, among others [2]. A study conducted by [51] shows the SEM analysis results, which showed a high C-S-H gel development, resulting in high strength after adding 6% of limited leather waste ash (LLWA) in a mix. EDX patterns showed a high formation of calcium silicate hydrate (C-S-H) gel after 28 days when the expansive soil was stabilized or treated with 20% GGBS [52].…”
Section: Microstructural Properties Of Treated Subgrade Materialsmentioning
confidence: 99%
“…Microstructural properties of materials can be determined in the laboratory by conducting a scanning electron microscopy (SEM) analysis, energy dispersive X-ray (EDX) analysis, radar detection, or a Mises strain test, among others [2]. A study conducted by [51] shows the SEM analysis results, which showed a high C-S-H gel development, resulting in high strength after adding 6% of limited leather waste ash (LLWA) in a mix. EDX patterns showed a high formation of calcium silicate hydrate (C-S-H) gel after 28 days when the expansive soil was stabilized or treated with 20% GGBS [52].…”
Section: Microstructural Properties Of Treated Subgrade Materialsmentioning
confidence: 99%